2004
DOI: 10.2337/diabetes.53.4.1150
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Gene Polymorphisms and Adiponectin Levels Are Independently Associated With the Development of Hyperglycemia During a 3-Year Period

Abstract: The plasma concentration of the adipocyte-derived peptide adiponectin is decreased in patients with obesity and type 2 diabetes. The adiponectin gene is located on chromosome 3q27, where a diabetes susceptibility locus has been mapped. Adiponectin gene polymorphisms (single nucleotide polymorphisms [SNPs]) have been associated with BMI, insulin sensitivity, and type 2 diabetes in some cross-sectional studies. Our aim was to assess the contribution of these SNPs in the development of features of the insulin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
139
4
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 23 publications
(25 reference statements)
9
139
4
5
Order By: Relevance
“…The present association study suggests that À11391A and À11377C carriers of 5 0 ADIPOQ gene variants could be prone to a higher regional fat increase over time in a general population. In contrast, Fumeron et al 22 found no association between the Adiponectin gene and weight gain G Dolley et al À11391G4A SNP and WHR at baseline and during the 3-year follow-up in their study in a population survey.…”
Section: Discussionmentioning
confidence: 78%
“…The present association study suggests that À11391A and À11377C carriers of 5 0 ADIPOQ gene variants could be prone to a higher regional fat increase over time in a general population. In contrast, Fumeron et al 22 found no association between the Adiponectin gene and weight gain G Dolley et al À11391G4A SNP and WHR at baseline and during the 3-year follow-up in their study in a population survey.…”
Section: Discussionmentioning
confidence: 78%
“…Heritability of adiponectin levels is 40-70% [8,9], and single nucleotide polymorphisms (SNPs) in the coding and 5′ sequences of the gene [9,10] define haplotypes at risk of type 2 diabetes that reduce adiponectin levels in diabetic and normoglycaemic populations [9,11]. These data show that low adiponectin level might be one of the primary determinants of type 2 diabetes, which is in part genetically determined, a hypothesis that we recently evidenced further in the prospectively followed French Caucasian DESIR population [12]. The PPARG agonists, glitazones, increase adiponectin levels, suggesting that part of their hypoglycaemic action is mediated by the hormone release [13].…”
Section: Introductionmentioning
confidence: 77%
“…These data corroborate those obtained in less obese subjects from different ethnic groups [9][10][11] and provide further evidence for the association of ACDC promoter SNP with the genetic modulation of adiponectinaemia and insulin sensitivity. Moreover, a prospective study in a general Caucasian population reported that genetic variations at the ACDC gene (including SNP −11,391) modulated adiponectin levels and increased the risk of becoming diabetic [12]. Although we could not detect an impact of ACDC promoter genetic variants on type 2 diabetes in non-obese subjects, they were closely associated with type 2 diabetes in obese (OR 1.73) and morbidly obese (OR 1.92) subjects, confirming the physiological role of adiponectin in the protection against the deleterious metabolic effects of an excess in corpulence.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, an adipokine, has been implicated in the pathogenesis of type 2 diabetes mellitus and nonalcoholic fatty liver disease (NAFLD), and appears to have many favorable effects on glucose and lipid metabolism [20,21]. It is positively correlated with insulin sensitivity and is decreased in obese and type 2 diabetic patients [22].…”
Section: Introductionmentioning
confidence: 99%